SXP 214: AN X-RAY PULSAR IN THE SMALL MAGELLANIC CLOUD, CROSSING THE CIRCUMSTELLAR DISK OF THE COMPANION - Hong, Jaesub; Antoniou, Vallia; Zezas, Andreas; Haberl, Frank; Drake, Jeremy J.; Plucinsky, Paul P.; Gaetz, Terrance; Sasaki, Manami; Williams, Benjamin; Long, Knox S.; Blair, William P.; Winkler, P. Frank; et al. (Astrophysical Journal, 2016)
Located in the Small Magellanic Cloud ( SMC), SXP 214 is an X-ray pulsar in a high mass X-ray binary system with a Be-star companion. A recent survey of the SMC under a Chandra X-ray Visionary program found that the source was in a transition when the X-ray flux was on a steady rise. The Lomb-Scargle periodogram revealed a pulse period of 211.49 +/- 0.42 s, which is significantly (> 5 sigma) shorter than the previous measurements made with XMM-Newton and RXTE. This implies that the system has gone through sudden spin-up episodes recently. The pulse profile shows a sharp eclipse-like feature with a modulation amplitude of >95%. The linear rise of the observed X-ray luminosity from less than or similar to 2x to 7 x 10(35) erg s(-1) is correlated with a steady softening of the X-ray spectrum, which can be described by the changes in the local absorption from N-H similar to 10(24) to less than or similar to 10(20) cm(-2) for an absorbed power-law model. The soft X-ray emission below 2 keV was absent in the early part of the observation when only the pulsating hard X-ray component was observed, whereas at later times, both soft and hard X-ray components were observed to be pulsating. A likely explanation is that the neutron star was initially hidden in the circumstellar disk of the companion, and later came out of the disk with the accreted material that continued fueling the observed pulsation.
Keywords: stars: neutron; X-rays: binaries